2001
DOI: 10.1554/0014-3820(2001)055[0834:mgafli]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Male Genotype Affects Female Longevity in Drosophila Melanogaster

Abstract: Several recent studies suggest that interactions with conspecific males can reduce the longevity of female Drosophila melanogaster or support the idea that male and female fitness components are involved in antagonistic interactions. Here we report that males from third-chromosome isogenic lines demonstrated significant genetic variation in male reproductive performance and in the longevity of their mates. Increased male performance was marginally significantly associated with one measure of increased female s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…When assaying P2 in D. pseudoobscura, Turner & Anderson (1984) found that first male genotype was a significant factor in determining P2 while second male genotype was not. If stronger selection on P1 than P2 is a more general phenomenon, and if the mechanisms underlying P1 and P2 are at least partially independent, as appears to be the case (Clark et al 1995;Civetta & Clark 2000;Sawby & Hughes 2001), we might expect P1 to be less variable than P2 in the changing environment of an ageing female reproductive tract.…”
Section: Discussionmentioning
confidence: 96%
“…When assaying P2 in D. pseudoobscura, Turner & Anderson (1984) found that first male genotype was a significant factor in determining P2 while second male genotype was not. If stronger selection on P1 than P2 is a more general phenomenon, and if the mechanisms underlying P1 and P2 are at least partially independent, as appears to be the case (Clark et al 1995;Civetta & Clark 2000;Sawby & Hughes 2001), we might expect P1 to be less variable than P2 in the changing environment of an ageing female reproductive tract.…”
Section: Discussionmentioning
confidence: 96%
“…Populations, as simple as laboratory island populations [8], have been found to harbor significant amount of genetic variation with respect to male’s ability to cause such mate-harm [47,48]. A number of previous studies have reported the selection response of mate-harm [22,24,25,28,43].…”
Section: Discussionmentioning
confidence: 99%
“…3500 adults per generation), wild-type population Ives (hereafter 'IV'), which has been cultured under standardized conditions for hundreds of generations ( [15]; electronic supplementary material). This population harbours considerable genetic variation for many traits, and has been used in a wide range of behavioural ecology and population genetics studies [5,16,21]. The population is cultured on a non-overlapping twoweek schedule, in which they are combined en masse every 14 days and distributed onto fresh media.…”
Section: Methodsmentioning
confidence: 99%